共同希望语言学院2023届汉语言本科专业学生对阅读兴趣与阅读困难的影响因素分析 - Jennie Hansela; Wiliyanti Then (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
This study investigates the level of interest in Chinese reading, the main difficulties encountered, and the influencing factors among undergraduate students majoring in Chinese Language at Harapan Bersama College of Languages, class of 2023. The research seeks to clarify how internal and external factors shape students motivation and reading performance, thereby contributing to the improvement of Chinese reading pedagogy in Indonesian higher education. A mixed descriptive–qualitative method was employed, integrating a Likert-scale questionnaire and semi-structured interviews with 122 respondents to identify patterns and interpret underlying causes. The collected data were analyzed through frequency statistics and thematic coding to ensure both quantitative and qualitative validity. The findings indicate that while students generally show a strong interest and positive attitude toward Chinese reading, difficulties related to vocabulary, grammar complexity, and insufficient background knowledge hinder comprehension. The study highlights that reading ability, emotional attitude, teacher and family support, and accessibility of reading materials significantly affect students reading engagement. These results emphasize the importance of developing differentiated reading materials, improving vocabulary instruction, and creating supportive reading environments to enhance students overall reading proficiency and long-term motivation.